Réponses

2014-10-03T17:32:12+02:00
Exercice 2
1) * signifie multipllié par
E = (2x+5)(3x-1)
E = 2x*3x + 2x*-1 +5*3x + 5*-1
E = 6x² -2x +15x -5
E = 6x²+13x-5

F = (3x-5)²
F = (3x-5)(3x-5)
F = 3x*3x +3x*-5 +(-5)*3x + (-5)(-5)
F = 9x²-15x-15x+25
F = 9x²-30x+25

G = (x-1)(x+1)
G = x*x + x*1 +(-1)*x + (-1)*1
G = x² +x-x-1
G = x²-1

H = (5x+2)²
H = (5x+2)(5x+2)
H = 5x*5x + 5x*2 + 2*5x + 2*2
H = 25x²+10x+10x+4
H = 25x²+20x+4

I = (x-3)² + (x+5)²
I = (x-3)(x-3) + (x+5)(x+5)
I = (x*x + x*-3 + (-3)*x + (-3)*(-3)) + (x*x + x*5 +5*x + 5*5)
I = (x²-3x-3x+9) + (x²+5x+5x+25)
I = x²-6x+9+x²+10x+25
I = 2x²+4x+34

2) X=-1
I = (-1-3)² + (-1+5)²
I = (-4)² + (4)²
I = 16+16
I = 32